Design of two-dimensional pseudorotated digital filters using concept of generalized immittance converter - Rameshwaran,, K; Eswaran,, C (2003)
A new realization procedure based on the concept of the generalized immittance converter (GIC) is proposed for two-dimensional (2D) pseudorotated digital filters that have circularly symmetric magnitude response characteristics. By applying a suitable transformation to a one-dimensional stable discrete transfer function, the 2D discrete transfer function of the corresponding pseudorotated filter is obtained. This transfer function is then realized by using a direct computer-based method. It is shown that four types of GIC pseudorotated filter structures can be obtained by interconnecting a few specific types of digital modules. The modularity and regularity nature of these filters make them attractive for very large-scale integration implementation.